CONSUMER UNDERSTANDING AND PERCEPTION OF MOUNTAIN LABEL IN THE CITY OF BRAȘOV, ROMANIA - Kiran MAINALI; Felix H. ARION; Cătălina ROGOZAN (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
The European Union introduced Regulation No. 1151/2012 to delineate the optional quality term "mountain product," aiming to preserve and promote the originality and authenticity of mountain foodstuffs. This research endeavors to delve into the comprehension and perception of the mountain label, considering awareness of the label and willingness to pay. With the remarkable increase in the adoption of the mountain label among producers in the mountain regions of Romania, this study seeks to investigate whether consumers purchasing the product in the market are cognizant of the provisions outlined by the National regulatory bodies and authorities for the mountain label. A general consumer survey with questionnaires was planned, organised, and implemented within Brașov city to elicit necessary findings. Although, the consumer was aware regarding the benefits associated with products with mountain label and also the places to easily find the mountain label, the consumers (50.77%) perceived mountain labelled product to be expensive. Similarly, only 47% of the respondents were interested in paying more for the products with mountain labels and 50% were completely unsure about their purchasing decisions, which indicates a clear unsurety in the mind of the consumers. The consumers (70%) seemed unaware about the mountain label although they had general idea regarding mountain products and the categories of products that are made available in the market verified by the agencies. The findings of this research can be beneficial to initiate different promotional campaigns launched at consumers to better educate them regarding mountain labels and to avoid misleading the consumer with any use of terms related with mountains and assist in overall mountain sustainability.